Retroperitoneoscopic debridement and internal fixation for the treatment of lumbar tuberculosis. Issue 37 (17th September 2021) - Tang, Yong; Ye, Jichao; Hu, Xumin; Yang, Wei
Abstract : Abstract: To describe the retroperitoneoscopic debridement technique and evaluate the clinical outcome of internal fixation for the treatment of lumbar tuberculosis. Twenty-eight patients were performed conventional laparoendoscopic technique (n = 17) or laparoendoscopic single-site technique (n = 11). Antituberculosis chemotherapy and thoracolumbosacral orthosis were given to all patients. The clinical outcomes were evaluated with preoperative and postoperative Visual Analog Scale, and radiographs with respect to sagittal angle and fusion status. Average time of the 28 procedures was 220.6 ± 50.9 min (180–365 min). The average intraoperative blood loss was 108.6 ± 95.3 mL (50–400 mL). All patients showed significant improvement of their Visual Analog Scale back pain score at follow-up and were classified as having a radiographic fusion in this study. The mean sagittal angle was 11.2 ± 3.6° before operation, significantly improved to 3.7 ± 2.4° after operation. There were no recurrent infections during the follow-up period. Complications included loosening of anterior fixation and temporary deficit of the sympathetic nerve. Retroperitoneal laparoscopic approach with CO2 insufflation technique is a challenging but safe and effective procedure for lumbar spine tuberculosis. Retroperitoneal laparoendoscopic single-site can be used for anterior lumbar spine surgery, offer exposure for L1 through L5.